Strategi Pengembangan Objek Wisata di Kabupaten Pati - Ratnasari, Fitrilia (Efficient: Indonesian Journal of Development Economics, 2018)
The objectives of this research are (1) to identify the profile and management system of tourism object in Pati Regency, (2) to identify the internal and external factors of tourism development in Pati Regency, (3) Prepare the development strategy of tourism object in Pati Regency. Data analysis technique using SWOT. The result of the research shows that (1) the tourism object profile in Pati Regency has great potential to be a tourist place that can bring many visitors with management system that need to be improved in order to establish good relationship between the Tourism Office and the management of the tourism object. (2) Internal factors that are owned by tourism object such as tourist attraction, hospitality, facilities, promotion and capital. While the external factors that are owned by tourism are competitiveness of tourism object, community life style, government support, innovation, and accommodation. (3) Strategy of tourism development in Pati Regency based on SWOT is the development of potential in each tourism object, maintenance and addition of facilities in tourism object, as well as increasing cooperation with private parties and investors. Tujuan dari penelitian ini adalah (1) mengidentifikasi profil dan sistem pengelolaan obyek wisata di Kabupaten Pati, (2) Mengidentifikasi faktor internal dan eksternal pengembangan obyek wisata di Kabupaten Pati, (3) Menyusun strategi pengembangan obyek wisata di Kabupaten Pati. Teknik analisis data menggunakan SWOT. Hasil penelitian menunjukkan bahwa (1) profil obyek wisata di Kabupaten Pati memiliki potensi yang sangat besar untuk dijadikan tempat wisata yang mampu mendatangkan banyak pengunjung dengan sistem pengelolaan yang perlu ditingkatkan agar menjalin hubungan yang baik antara Dinas Pariwisata dan pengelola obyek wisata. (2) Faktor internal yang dimiliki obyek wisata antara lain daya tarik wisata, keramahtamahan, fasilitas, promosi dan modal. Sedangkan faktor eksternal yang dimiliki obyek wisata adalah daya saing obyek wisata, gaya hidup masyarakat, dukungan pemerintah, inovasi, serta akomodasi. (3) Strategi pengembangan obyek wisata di Kabupaten Pati berdasarkan SWOT adalah pengembangan potensi di masing-masing obyek wisata, pemeliharaan dan penambahan fasilitas di obyek wisata, serta meningkatkan kerjasama dengan pihak swasta maupun investor.